REPRESENTAÇÕES SOCIAIS DE PROFESSORES DO ENSINO FUNDAMENTAL SOBRE ALUNOS COM DEFICIÊNCIA E A EDUCAÇÃO INCLUSIVA - KITAHARA, ADIL MARGARETE VISENTINI (2018)
This doctoral thesis investigated the Social Representations of Elementary School Teachers about students with disabilities and Inclusive Education in the Municipal Schools of Primary Education of the Municipal Network of the City of São Paulo. The Theory of Social Representations of Serge Moscovici was used. We analyzed the Social Representations that teachers have of students with disabilities and how these representations have repercussions on the practice of teaching. Exploratory research with a qualitative method was used in interviews and focus groups. Sixteen teachers were interviewed and two focus groups were held. The analysis and interpretation of the interviews and focus groups addressed topics focused on professional training, on the discernment of different pathological nomenclatures and their specificities, information exchange among peers, help places and pedagogical support for their students, as well as pedagogical practices. The following difficulties were identified: the lauded students and the identification of the non-lauded ones, the understanding and the procedure before the pathology, the number of students in class, lack of trainees / auxiliary teachers, lack of less bureaucratic skills and more directed towards inclusion and the barrier of prejudice. The Social Representations of the teachers before students with disabilities mobilized practices of inclusive education, such as: the records of the activities developed and the shared teaching. It was observed that the learning process should be attentive to the confrontation of prejudices and the development of pedagogical practices with the use of digital technologies. Inclusive Education of students with disabilities is part of the larger process, Social Inclusion, which goes beyond the school scope and must guarantee universalization of access and quality of socio-educational contexts for all.